2019
DOI: 10.1097/corr.0000000000000824
|View full text |Cite
|
Sign up to set email alerts
|

How Well Represented Are Women Orthopaedic Surgeons and Residents on Major Orthopaedic Editorial Boards and Publications?

Abstract: Background Recent studies indicate that women are substantially underrepresented as orthopaedic surgeons and residents compared with other specialties in medicine and medical school. The reasons for this are multifactorial and not completely understood, but previous studies suggest that women may be attracted to fields in which they have female role models. Given that women interested in academia and research may use female editorship and authorship as a proxy for female representation in orthopaed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 8 publications
5
53
0
2
Order By: Relevance
“…From 1987 to 2017, 1.7% of senior authors and 4.4% of first authors of orthopaedic publications were female 33 . There has never been a female editor-in-chief of the 3 major orthopaedic journals 34 . The majority of women have academic rank of instructor, with only 8.7% achieving full professor 35 .…”
Section: Discussionmentioning
confidence: 99%
“…From 1987 to 2017, 1.7% of senior authors and 4.4% of first authors of orthopaedic publications were female 33 . There has never been a female editor-in-chief of the 3 major orthopaedic journals 34 . The majority of women have academic rank of instructor, with only 8.7% achieving full professor 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This is very encouraging and seems to demonstrate that the gender gap is being slowly closed. A recent study [ 150 ] noted that women were represented equally or in greater numbers as editors in JBJS, Journal of the American Academy of Orthopaedic Surgeons , and Clinical Orthopaedics and Related Research. They noted the same lag that we did when comparing editors to authors, with the percentage of female editors in 2017 roughly equaling the percentage of female authors in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…The skills and specific training required to become physician leaders in surgical fields, 3,8,11 predictors of physician leaders, 2 and the role of characteristic variations in position selection and specialty representation have also been explored in the context of orthopaedics. 6,12,13 Recently, a cross-sectional study identifying leadership trends in spine surgery fellowships demonstrated that fellowship directors (FDs) are more likely to have graduated from certain residency and fellowship programs. 4 While these trends have been identified in orthopaedic spine surgery, there is no current literature describing these trends in sports medicine or any other orthopaedic subspecialty.…”
mentioning
confidence: 99%